Samarra and the Spatial Politics of Power: Reassessing the Abbasid Capital Relocation under al-Mu‘taṣim - Akhmad Najibul Khairi Syaie; Haukil Hannan; Ahmad Syafi'ie Hadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The relocation of the Abbasid capital from Baghdad to Samarra in 836 CE under Caliph al-Mu‘taṣim has long been interpreted as a decisive administrative maneuver that temporarily redefined the geography of Islamic governance. However, prevailing narratives often overlook the deeper political complexities and long-term ramifications of this move. This article seeks to reassess the motivations behind al-Mu‘taṣim’s decision and critically examine the consequences of transferring the seat of power to Samarra. Employing a historical-analytical methodology grounded in primary and secondary sources, the study interrogates factors such as military exigencies, personal predilections, and the caliph’s broader political calculus. The findings reveal that while Samarra emerged as a militarized enclave catering to the needs of the Turkish guard, it failed to eclipse Baghdad’s enduring political and symbolic centrality. The relocation inadvertently exacerbated factionalism and destabilized the caliphal institution, particularly under al-Mu‘taṣim’s successors. This article concludes that the capital shift did not yield the strategic coherence envisioned by its architect and, instead, exposes the fragility of centralized authority within the Abbasid polity. By reevaluating a pivotal yet understudied episode in Abbasid history, the study contributes to broader discussions on urban relocation, imperial governance, and the limits of caliphal power. Further research is needed to explore the longue durée implications of Samarra’s decline for subsequent Islamic political configurations.